ANALISIS ABNORMAL RETURN SAHAM SEBELUM DAN SESUDAH REVERSE STOCK SPLIT PADA PERUSAHAAN DI BEI PERIODE 2011-2015 - Kusdarmawan, Putu Aris; Abundanti, Nyoman (E-Jurnal Manajemen; Vol 7 No 7 (2018)DO - 10.24843/EJMUNUD.2018.v07.i07.p14, 2018)
A positive stock return causes investors interested and interested in investing in the company that issued the shares. Many companies do stock split to overcome the problem too low or too high stock prices. This study aims to analyze whether there are significant differences abnormal return of stock before and after conducted reverse stock split on company in BEI. The population in this study is the company that conducted reverse stock split in 2011 to 2015. Purposive sampling is the method used in sampling and obtained a number of 6 issuers meet the criteria of the sample. Tests in this study used the approach of event study and analytical techniques used to test bedaabnormal share return before and after reverse stock split is non-parametric test: wilcoxon signed rank test because the data is not normally distributed. The result obtained from this research is there is no significant difference of abnormal return of stock before and after announcement of reverse stock split. The result can be interpreted that the market does not respond to the stock split stocks. The stock split does not have information content and is not considered important information for investors.